The Gut Microbiota and Inflammatory Bowel Diseases - Miyoshi, Jun (Transl Res, 2016)
Inflammatory bowel diseases (IBD) are chronic diseases of unclear etiology that affect over 1 million individuals in the United States and over 2.5 million people in Europe(1). However, they are also expanding globally, affecting populations in Asia, South America, and the Middle East as they become more industrialized. These diseases are believed to arise from the convergence of genetic, environmental, and microbial factors that trigger aberrant immune and tissue responses, resulting in intestinal inflammation. Advances in cultivation-independent investigations, experimental models, and bioinformatics approaches have improved our understanding of the role of gut microbiota in IBD. However, determining and understanding the functional consequences of gut dysbiosis and altered host-microbiota interactions in IBD remain a challenge due to the limits of current experimental models and difficulty in establishing causal links in human-based investigations. Continued development of new methodologies and improvements in clinical study design are needed to better understand the interplay of genetic, microbial, and immunological factors in IBD. This knowledge can then be applied clinically to improve therapeutic strategies and outcomes for IBD.